The Impact of Multidisciplinary Discussion (MDD) in the Diagnosis and Management of Fibrotic Interstitial Lung Diseases. (17th August 2020) - Ageely, Ghofran; Souza, Carolina; De Boer, Kaissa; Zahra, Saly; Gomes, Marcio; Voduc, Nha
Abstract : Accurate diagnosis of interstitial lung disease (ILD) is crucial for management and prognosis but can be challenging even for experienced clinicians. Expert multidisciplinary discussion (MDD) is considered the reference standard for ILD diagnosis; however, there remain concerns regarding lack of validation studies and relative limited information on the impact of MDD in real-life clinical practice. The goal of this study was to assess the effect of MDD in providing a specific ILD diagnosis, changing the diagnosis provided upon referral, and to determine how often and in which way MDD altered management. Material and Methods . Retrospective observational study in an ILD referral tertiary academic center. MDD diagnoses were categorized as specific, provisional, and unclassifiable ILD. Pre-MDD and MDD diagnoses were compared for change in diagnosis and concordance rates for specific diagnoses. Relevant change in management including initiation or change in pharmacological treatment, referral to surgical biopsy, and nonpharmacological management were recorded. Results . 126 cases were included (79M, 47F, 36–93 years, mean 70 y). Specific MDD diagnosis was provided in 62% (78/126); 12% (15/126) had provisional diagnosis, and 21% (27/126) was unclassifiable. Overall agreement for specific pre-MDD and MDD diagnosis was 41% (52/126) and 80% for idiopathic pulmonary fibrosis (IPF) diagnosis. MDD altered diagnosis in 37% (47/126) and changed management in 39% (50/126). Amongst concordant diagnoses, management was altered in 46% (24/52). In summary, MDD provided a specific diagnosis discordant with pre-MDD diagnosis in a significant proportion of cases and was particularly valuable in the diagnosis of non-IPF ILD. MDD often altered management and had relevant impact on management even in cases with concordant pre-MDD diagnosis.